1995
DOI: 10.1111/j.1600-0447.1995.tb05923.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and selective inhibitors of monoamine oxidase A in mental and other disorders

Abstract: The clinically tested reversiblc inhibitors of monoamine oxidase A (RIMAs) include brofaromine, moclobemide and toloxatone. Moclobemide has shown unequivocal antidepressant activity against serious deprcssivc illness in 4 placebo‐controlled double‐blind trials. It has been compared with amitriptyline, imipramine, clomipramine, desipramine, maprotiline, fluoxetine, fluvoxamine, tranylcypromine. toloxatone, mianserin and amineptine in the treatment of depressive disorders. Meta‐analysis showed convincing evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Future work on MAO inhibitors was driven by two aspects: first, the search for safer, reversible inhibitors of MAO and, second, differentiation of MAO-A, which mainly metabolizes 5-HT and NA, from MAO-B which preferentially metabolizes DA and phenethylamines like tyramine (Lotufo-Neto et al, 1999;Priest et al, 1995). This work resulted in the launch of the reversible and well-tolerated MAO-A inhibitor moclobemide in the EU for the treatment of depression and social anxiety (Kriston et al, 2014;Lotufo-Neto et al, 1999).…”
Section: Monoamine Oxidase Inhibitors: Irreversible To Reversiblementioning
confidence: 99%
“…Future work on MAO inhibitors was driven by two aspects: first, the search for safer, reversible inhibitors of MAO and, second, differentiation of MAO-A, which mainly metabolizes 5-HT and NA, from MAO-B which preferentially metabolizes DA and phenethylamines like tyramine (Lotufo-Neto et al, 1999;Priest et al, 1995). This work resulted in the launch of the reversible and well-tolerated MAO-A inhibitor moclobemide in the EU for the treatment of depression and social anxiety (Kriston et al, 2014;Lotufo-Neto et al, 1999).…”
Section: Monoamine Oxidase Inhibitors: Irreversible To Reversiblementioning
confidence: 99%
“…The reversible inhibitors of monoamine oxydase, brofaromine and moclobemide were recently introduced into therapy to minimize the risk of serious adverse reactions associated with the irreversible MAOIs. Clinical trials have shown these drugs to be effective antipanic agents [20,83,99,101]. SSRIs are active in reducing panic symptomatology and are better tolerated than BZs, tricyclic antidepressants and MAOIs.…”
Section: Panicolytic and Panicogenic Agentsmentioning
confidence: 99%
“…buspirone and tandospirone) (Barradell and Fitton, 1996;Fulton and Brogden, 1997). In addition, only selective 5-HT re-uptake and monoamine-oxidase inhibitors have been successfully used in the chronic treatment of panic attacks, obsessive -compulsive, and posttraumatic stress disorders (Billett et al, 1997;Buller, 1995;Fichtner et al, 1997;Liebowitz et al, 1990;Priest et al, 1995;Westenberg, 1996). Although interest in this research area has steadily decreased, novel 5-HT-modulating agents are still being developed.…”
Section: Selective and Nonselective 5-ht-interacting Drugsmentioning
confidence: 99%